SOSIALISASI KREATIVITAS MAHASISWA INDO GLOBAL MANDIRI KEGIATAN PIDAL KAYU (PINUS DESIGN LIMBAH KAYU) PKM KEWIRAUSAHAAN GUNA MENDUKUNG MBKM - Nur Syabitha, Fidya; Tsabita, Putri; Hertati, Lesi; Terttiaavini; Heryati, Agustina; Asmawati (Transpublika Publisher, 2021)
This research aimed to utilize pine wood waste generated from furniture production that is no longer in use. The waste consists of small pieces of wood that can be repurposed into new products. The design process focused on creating souvenirs that align with the material's characteristics. The objective was to transform the pine wood waste into small-sized products with market value. The research was conducted in several stages, including data and information collection from furniture workshops in Palembang. Alternative designs were then developed and represented in 3-dimensional digital models, followed by the creation of prototypes using the pine wood waste. The results include several new design alternatives, representing souvenir products for families. These findings are expected to offer opportunities for the furniture business to explore new ventures using previously discarded materials.